Impact of wildfire on 137Cs and 90Sr wash-off in heavily contaminated forests in the Chernobyl exclusion zone. (April 2020) - Igarashi, Yasunori; Onda, Yuichi; Wakiyama, Yoshifumi; Konoplev, Alexei; Zheleznyak, Mark; Lisovyi, Hlib; Laptev, Gennady; Damiyanovich, Volodyill; Samoilov, Dmitry; Nanba, Kenji; Kirieiev, Serhii
Abstract: Wildfires may play a role in redistributing radionuclides in the environment in combination with hydrological processes such as surface runoff and soil erosion. We investigated plot-scale radionuclide wash-off at forest sites affected by wildfires in the Chernobyl Exclusion Zone (CEZ). We also compared speciation of the washed-off radionuclides with those in previous studies conducted just after the accident in 1986. We observed the surface runoff and the radionuclide wash-off with a soil erosion plot at forest and post-fire sites during May–September 2018. In the post-fire site, 2.81 mm of surface runoff was observed in at least three flow events resulting from 285.8 mm total rainfall. The fluxes of dissolved and particulate 137 Cs were estimated as 4.9 and 161 Bq m −2, respectively. The dissolved phase 90 Sr flux was estimated as 214 Bq m −2 . At the forest site, a single surface runoff (0.67 mm) event was generated by rainfall of 182.2 mm. The fluxes of dissolved and particulate 137 Cs wash-off values were 6.2 and 8.6 Bq m −2, respectively. The flux of dissolved 90 Sr wash-off from the forest was estimated as 45.1 Bq m −2 . The distribution coefficient, which indicates the dissolved-particulate form of radionuclides, in the post-fire site was 30 times higher than that in the forest site, indicating the importance of particulate 137 Cs wash-off after fire in the CEZ. The entrainment coefficients for dissolved and particulate 137 Cs concentrations were around 50 times lower than those obtained in the corresponding position within the CEZ immediately after the accident in 1987. The effect of downward migration of 137 Cs over 30 years led to decreased entrainment coefficients for dissolved and particulate 137 Cs. The effect of downward migration of radionuclides was considered sufficient to indicate changes in normalized liquid and solid radionuclides wash-off entrainment coefficient and the distribution coefficient in this study. Graphical abstract: Image 1 Highlights: Radionuclide wash-off was observed from a post-fire site in the CEZ. K d in the post-fire site was 30 times higher than that in the undisturbed forest site. Particulate 137 Cs wash-off is important after fire. The downward migration effect decreased N l ( 137 Cs) and N s ( 137 Cs) during the 30-years.